Identification of atrogin-1-targeted proteins during the myostatin-induced skeletal muscle wasting - Lokireddy, Sudarsanareddy (2013)
Atrogin-1, a muscle-specific E3 ligase, targets MyoD for degradation through the ubiquitin-proteasome-mediated system. Myostatin, a member of the transforming growth factor-β superfamily, potently inhibits myogenesis by lowering MyoD levels. While atrogin-1 is upregulated by myostatin, it is currently unknown whether atrogin-1 plays a role in mediating myostatin signaling to regulate myogenesis. In this report, we have confirmed that atrogin-1 increasingly interacts with MyoD upon recombinant human myostatin (hMstn) treatment. The absence of atrogin-1, however, led to elevated MyoD levels and permitted the differentiation of atrogin-1−/− primary myoblast cultures despite the presence of exogenous myostatin. Furthermore, inactivation of atrogin-1 rescued myoblasts from growth inhibition by hMstn. Therefore, these results highlight the central role of atrogin-1 in regulating myostatin signaling during myogenesis. Currently, there are only two known targets of atrogin-1. Thus, we next characterized the associated proteins of atrogin-1 in control and hMstn-treated C2C12 cell cultures by stably expressing tagged atrogin-1 in myoblasts and myotubes, and sequencing the coimmunoprecipitated proteome. We found that atrogin-1 putatively interacts with sarcomeric proteins, transcriptional factors, metabolic enzymes, components of translation, and spliceosome formation. In addition, we also identified that desmin and vimentin, two components of the intermediate filament in muscle, directly interacted with and were degraded by atrogin-1 in response to hMstn. In summary, the muscle wasting effects of the myostatin-atrogin-1 axis are not only limited to the degradation of MyoD and eukaryotic translation initiation factor 3 subunit f, but also encompass several proteins that are involved in a wide variety of cellular activities in the muscle.